2000
DOI: 10.1002/(sici)1097-0134(20000401)39:1<89::aid-prot10>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity and steric strain in a parallel ?-helix: Rational mutations in the P22 tailspike protein

Abstract: By means of genetic screens, a great number of mutations that affect the folding and stability of the tailspike protein from Salmonella phage P22 have been identified. Temperature-sensitive folding (tsf) mutations decrease folding yields at high temperature, but hardly affect thermal stability of the native trimeric structure when assembled at low temperature. Global suppressor (su) mutations mitigate this phenotype. Virtually all of these mutations are located in the central domain of tailspike, a large paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 59 publications
(76 reference statements)
0
9
0
Order By: Relevance
“…Mutational (33,34) and sequence analyses (35) have shown that the ␤-helix topology is highly tolerant of sequence variations. In addition, because the ␤-helix is a processive fold, larger proteins (or larger active sites) can be accommodated simply by increasing the number of rungs or extending one or more loops to form a functional domain [as seen for hemoglobin protease (11)], while still preserving the ␤-helix core.…”
Section: Discussionmentioning
confidence: 99%
“…Mutational (33,34) and sequence analyses (35) have shown that the ␤-helix topology is highly tolerant of sequence variations. In addition, because the ␤-helix is a processive fold, larger proteins (or larger active sites) can be accommodated simply by increasing the number of rungs or extending one or more loops to form a functional domain [as seen for hemoglobin protease (11)], while still preserving the ␤-helix core.…”
Section: Discussionmentioning
confidence: 99%
“…It is tempting therefore to point to the passenger C-terminus as the crucial region that determines whether an endogenous AT passenger is compatible with AT secretion, but it should be noted that premature formation of stable folded structures at the N-terminus of an endogenous passenger can also reduce its secretion efficiency (Jong et al, 2007; Leyton et al, 2011; Renn et al, 2012; Saurí et al, 2012). Moreover, many of these less conserved passenger N-terminal sequences still adopt a β-helical fold, likely reflecting the plasticity of the β-helical fold to amino acid substitutions (Schuler et al, 2000). …”
Section: Common Themes (And Variations) For Characterized Autotranspomentioning
confidence: 99%
“…Schuler et al concluded that the parallel b-helix core of P22 tailspike protein accommodates destabilizing mutations through packing adjustments within the lumen of the b-helix. 48 It may not be coincidental that this parallel b-helix structure is a motif that has been implicated as a possible generic fold for amyloid fibrils. [49][50][51] The plasticity suggested by the double mutant cycle data ( Figure 6) may be providing clues to the mysterious ability of many proteins to form stable amyloid fibrils, 52 despite having evolved to optimize a completely different folded structure.…”
Section: Plasticity In Amyloid Fibrilsmentioning
confidence: 99%